A case report of percutaneous successful closure of multiple atrial septal defect - Jia, Lili (J Cardiol Cases, 2011)
A 50-year-old male patient with a secundum-type atrial septal defect (ASD) suffering from respiratory distress for 7 days was referred to our hospital. Transthoracic echocardiography demonstrated the defects of 9 mm and 4 mm in the middle atrial septum in the parasternal four-chamber view. However, we found not 2, but 6 atrial defects by using real time 3-dimensional transesophageal echocardiography. Open heart surgery was not indicated, because his pulmonary function was poor. After fully informed consent, we decided to treat ASD with Amplatzer septal occluders.